Surface microstructural design to improve mechanical and giant magneto-impedance properties of melt-extracted CoFe-based amorphous wires. (June 2021) - Jiang, Sida; Wang, Huan; Estevez, Diana; Huang, Yongjiang; Zhang, Lunyong; Shen, Hongxian; Ning, Zhiliang; Qin, Faxiang; Sun, Jianfei
Abstract: The influence of surface microstructural regulation mechanisms on the mechanical and giant magneto-impedance (GMI) properties of as-cast melt-extracted CoFe-based wires has been systematically researched based on morphology, phase distribution and domain structure parameters. A series of statistical models were applied to analyze the mechanical properties and followed by mapping the curve of cumulative failure rate for wire application. It was found that the average and highest fracture strengths, average tensile strain increased with Cu substitution and reached peaks of ~3725 MPa, ~4250 MPa and ~2.7%, respectively. Verified structure-simulation experiments revealed that surface Rayleigh waves effectively split the main crack and the diffusely distributed nanocrystalline in surface area acted as a pinning point to impede the crack growth, enhancing the mechanical properties. The GMI ratio displayed similar variations and attained a maximum value of 700 ± 5% as well as the resistance and reactance ratios improved to ~687% and ~2206%, respectively. The enhanced relative dielectric permeability μ s resulting from the increased domain wall energy density and the decreased surface domain width. The unique synchronous enhancement of CoFe-based wires satisfies the demand for emerging magnetoelectric sensor applications, e.g. flexible and wearable sensors, equipment self-monitoring sensors, and array robotic skin sensors under harsh working environments. Graphical abstract: Unlabelled Image Highlights: Surface microstructural design of melt-extracted CoFe-based amorphous wires were systematically researched. The relationship between surface nanoscale Rayleigh waves and domain structure was established. Enhanced mechanisms of mechanical and giant magneto-impedance (GMI) properties were clarified. Highest fracture strengths and tensile strain enhanced to ~4250 MPa and ~2.7%, and GMI ratio improved to 700 ± 5%.